Energy-dependent immunity protein release during tol-dependent nuclease colicin translocation. - Vankemmelbeke, M; Zhang, Y; Moore, G; Kleanthous, K; Penfold, C; James, R (2009)
Nuclease colicins bind their target receptor in the outer membrane of sensitive cells in the form of a high affinity complex with their cognate immunity proteins. Upon cell entry the immunity protein is lost from the complex by means that are poorly understood. We have developed a sensitive fluorescence assay that has enabled us to study the molecular requirements for immunity protein release. Nuclease colicins use members of the tol operon for their translocation across the outer membrane. We have demonstrated that the amino-terminal 80 residues of the colicin E9 molecule, which is the region that interacts with TolB, are essential for immunity protein release. Using tol deletion strains we analyzed the cellular components necessary for immunity protein release and found that in addition to a requirement for tolB, the tolA deletion strain was most affected. Complementation studies showed that the mutation H22A, within the transmembrane segment of TolA, abolishes immunity protein release. Investigation of the energy requirements demonstrated that the proton motive force of the cytoplasmic membrane is critical. Taken together these results demonstrate for the first time a clear energy requirement for the uptake of a nuclease colicin complex and suggest that energy transduced from the cytoplasmic membrane to the outer membrane by TolA could be the driving force for immunity protein release and concomitant translocation of the nuclease domain.